Wheat Stem Rust Surveillance Reveals Two New Races of Puccinia graminis f. sp. tritici in South Africa During 2016 to 2020 - Terefe, Tarekegn G (Plant disease, 2024)
Stem rust, caused by Puccinia graminis f. sp. tritici (Pgt), is an important disease of wheat in South Africa (SA) and is primarily controlled using resistant cultivars. Understanding virulence diversity of Pgt is essential for successful breeding of resistant cultivars. Samples of infected wheat stems were collected across the major wheat-growing regions of SA from 2016 to 2020 to determine the pathogenic variability of Pgt isolates. Seven races were identified from 517 isolates pathotyped. The most frequently found races were 2SA104 (BPGSC + Sr9h,27,Kw) (35% frequency) and 2SA88 (TTKSF + Sr8b) (33%). Race 2SA42 (PTKSK + Sr8b), which was found in 2017, and 2SA5 (BFGSF + Sr9h), identified in 2017, are new races. The Ug99 variant race 2SA42 is similar in its virulence to 2SA107 (PTKST + Sr8b) except for avirulence to Sr24 and virulence to Sr8155B1. Race 2SA5 is closely related in its virulence to existing races that commonly infect triticale. Certain races showed limited geographical distribution. Races 2SA5, 2SA105, and 2SA108 were found only in the Western Cape, whereas 2SA107 and 2SA42 were detected only in the Free State province. The new and existing races were compared using microsatellite (SSR) marker analysis and their virulence on commercial cultivars was also determined. Seedling response of 113 wheat entries against the new races, using 2SA88, 2SA88+9h, 2SA106, and 2SA107 as controls, revealed 2SA107 as the most virulent (67 entries susceptible), followed by 2SA42 (64), 2SA106 (60), 2SA88+9h (59), 2SA88 (25), and 2SA5 (17). Thus, 2SA5 may not pose a significant threat to local wheat production. SSR genotyping revealed that 2SA5 is genetically distinct from all other SA Pgt races